Peran Guru dalam Membina Karakter Siswa di Sekolah Menengah Pertama - Uswatun Khasanah, Nurul; Mufidatuzzulfa, Nisa; Syaifuddin, Mohammad (Jurnal Bintang Pendidikan Indonesia, 2025)
The teacher is an important figure for students in school. The s uccess of education is determined by the human element, one of which is the teacher. As an educator the teacher has a great responsibility for the character of his students so that they are accustomed to doing good The formulation of the research problem is what efforts do teachers make in building character at SMPN 2 Talun ? What is the condition of the student’s character with the character fostered by the teacher at SMPN 03 Karangdadap? The purpose of this study was to reveal what efforts the teacher made in fostering student character at SMPN 2 Talun . Based on the results of the research, it shows that: the role of a teacher in fostering the character of students at SMPN 2 Talun is that the teacher acts as a motivator, this can be seen from the efforts of educators to do the right thing. This is indicated by the emergence of awareness in a child of what is being done and the enthusiasm of a student in activities at the madrasah.